2017
DOI: 10.1016/j.aller.2016.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Effect of phototherapy on B and T lymphocytes in Egyptian infants suffering from neonatal jaundice

Abstract: The study showed a significant difference in CD19+ lymphocytes percentage between patients before phototherapy and controls (P value<0.01), also a significant correlation between serum levels of total bilirubin in patients and CD19+ lymphocytes percentage (P value<0.05). There was no significant difference between the percentages of CD19+, CD4+ and CD8+ lymphocytes in patients before or after 72h of exposure to phototherapy (P value>0.05). Also, there was no correlation between the percentages of CD19+, CD4+ a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…Recently, many researchers have proposed that the immunogenic death effect resulting from the traditional treatments, and innate immunity elicited by immune agonists or microorganisms could efficiently improve the antitumor effect of ICB therapy . However, the immune system damage induced by traditional treatments and autoimmunity evoked by agonists or microorganisms cannot be ignored …”
Section: Methodsmentioning
confidence: 99%
“…Recently, many researchers have proposed that the immunogenic death effect resulting from the traditional treatments, and innate immunity elicited by immune agonists or microorganisms could efficiently improve the antitumor effect of ICB therapy . However, the immune system damage induced by traditional treatments and autoimmunity evoked by agonists or microorganisms cannot be ignored …”
Section: Methodsmentioning
confidence: 99%
“…To date, the effects of PT on eosinophils, platelets, T and B lymphocytes have been investigated in some studies. 3,4 To the best of the authors' knowledge, there is no study in the literature that focuses on relationship between neutrophil volume, conductivity and scatter (VCS) parameters and PT in jaundiced newborns. Some authors proposed that the morphologic changes seen in neutrophils in sepsis could be analysed by using the Coulter LH 750 with VCS technology.…”
Section: Introductionmentioning
confidence: 99%
“…Kurt et al observed a increase in IL‐8, IL‐1beta, and TNF‐alfa levels and a decrease in the percentage of T‐cell lymphocytes. Rashedyet et al did not find alterations in CD4+ T‐cell, CD8+ T‐cell, or NK‐cell lymphocyte subsets after phototherapy, as well as in the study by Eyada et al , who did not find significant differences in the percentage of CD4+ T‐cell, CD8+ T‐cell, or B‐cell lymphocyte subsets before and after phototherapy. To our knowledge, ours is the first study evaluating the expression of neutrophil surface markers in icteric neonates undergoing phototherapy treatment using flow cytometry.…”
Section: Discussionmentioning
confidence: 99%